Mobile Controlled Robots (International Journal of Engineering and Computer Science, 2017)
Conventionally, Wireless-controlled robots use rf circuits, which have the drawbacks of limited working range, limited frequency range and the limited control. Use of a mobile phone for robotic control can overcome these limitations. It provides the advantage of robust control, working range as large as the coverage area of the service provider, no interference with other controllers and up to twelve controlles. The key function of these robots is their ability to communicate with humans. Since communication via mobile phones is becoming increasingly common among us, it is essential for these robots also to be able to communicate using mobile phones. In this paper we propose the concept of a home robot and describe the essential functions that we consider are essential for the robot. Although the appearance and the capabilities of robots vary vastly, all robots share the feature of a mechanical, movable structure under some form of control. The Control of robot involves three distinct phases: perception, processing and action. Generally, the preceptors are sensors mounted on the robot, processing is done by the on-board microcontroller or processor, and the task is performed using motors or with some other actuators.